2022
DOI: 10.1292/jvms.22-0119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of changed proteins by retinoic acid in cerebral ischemic damage: a proteomic study

Abstract: Ischemic stroke is a severe neurodegenerative disease with a high mortality rate. Retinoic acid is a representative metabolite of vitamin A. It has many beneficial effects including anti-inflammatory, antiapoptotic, and neuroprotective effects. The purpose of this study is to identify specific proteins that are regulated by retinoic acid in ischemic stroke. Middle cerebral artery occlusion (MCAO) was performed to induce focal cerebral ischemia. Retinoic acid (5 mg/kg) or vehicle was injected intraperitoneally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…[49] Similarly, retinoic acid was found to perform neuroprotective function by regulating various proteins that mediate cell metabolism and function such as Ahcy, Idh3a, and Gpd1. [61] A label-free proteomic study found that the tyrosine metabolism and dopaminergic synapse signaling pathways were disrupted in MCAO rats, and glutathione treatment restored protein expression to normal levels. Western blot validation and metabolite quantification showed that the mechanism underlying the therapeutic effects of glutathione on AIS was to increase intrastriatal dopamine through reversal of AIS-induced downregulation of tyrosine hydroxylase.…”
Section: Proteomics Studies Of Acute Ischemic Stroke In Animal Modelsmentioning
confidence: 99%
“…[49] Similarly, retinoic acid was found to perform neuroprotective function by regulating various proteins that mediate cell metabolism and function such as Ahcy, Idh3a, and Gpd1. [61] A label-free proteomic study found that the tyrosine metabolism and dopaminergic synapse signaling pathways were disrupted in MCAO rats, and glutathione treatment restored protein expression to normal levels. Western blot validation and metabolite quantification showed that the mechanism underlying the therapeutic effects of glutathione on AIS was to increase intrastriatal dopamine through reversal of AIS-induced downregulation of tyrosine hydroxylase.…”
Section: Proteomics Studies Of Acute Ischemic Stroke In Animal Modelsmentioning
confidence: 99%